QR CODES IN THE PROFESSION OF TEACHER - Benediktova, Lenka; Sedlacko, Filip (Journal of Technology and Information Education, 2024)
The acronym "QR code" means Quick Response code in translation. In our article we focus on whether or not they can be effectively used in teacher's profession, meaning not only during lessons. QR codes are used to load certain information with the help of a smart device (tablet, mobile phone). In this article we try to find out how these codes can be used to improve teacher's lessons. Further we focus on how to use these codes in school in general, outside of lessons. Are they suitable for field trips? Can teachers use them in other parts of their profession, for example in educational or career counseling? And how can we use them properly so that they really improve the work? The goal of this article is to come up with suitable strategies for using QR codes on elementary schools. To obtain more information we a researched both foreign and domestic sources and we also did our own research - half structured interviews to find out, whether or not teachers use the QR codes in lessons and if so, in which way. It is obvious that QR codes are appropriate tool for teachers to use in lessons or even outside of lessons. If methodical support is provided, QR codes appear to be fitting addition to teacher's profession.
Keywords: QR codes; BYOD; elementary school; digital technology; research; teaching strategies.